Metal Nanoparticles to Combat Candida albicans Infections: An Update - Carmo, Paulo Henrique Fonseca do [UNESP]; Garcia, Maíra Terra [UNESP]; Figueiredo-Godoi, Lívia Mara Alves [UNESP]; Lage, Anna Carolina Pinheiro; Silva, Newton Soares da [UNESP]; Junqueira, Juliana Campos [UNESP] (MDPI, 2023)
Candidiasis is an opportunistic mycosis with high annual incidence worldwide. In these infections, Candida albicans is the chief pathogen owing to its multiple virulence factors. C. albicans infections are usually treated with azoles, polyenes and echinocandins. However, these antifungals may have limitations regarding toxicity, relapse of infections, high cost, and emergence of antifungal resistance. Thus, the development of nanocarrier systems, such as metal nanoparticles, has been widely investigated. Metal nanoparticles are particulate dispersions or solid particles 10–100 nm in size, with unique physical and chemical properties that make them useful in biomedical applications. In this review, we focus on the activity of silver, gold, and iron nanoparticles against C. albicans. We discuss the use of metal nanoparticles as delivery vehicles for antifungal drugs or natural compounds to increase their biocompatibility and effectiveness. Promisingly, most of these nanoparticles exhibit potential antifungal activity through multi-target mechanisms in C. albicans cells and biofilms, which can minimize the emergence of antifungal resistance. The cytotoxicity of metal nanoparticles is a concern, and adjustments in synthesis approaches or coating techniques have been addressed to overcome these limitations, with great emphasis on green synthesis.
Keywords: antifungal agent; Candida albicans; gold; iron; metal nanoparticles; silver